Importance of Libraries in Tertiary Institutions: A Case Study of St. John Bosco Primary Teachers’ College Library, Yumbe District. - Bonniface, Agungi (Kabale University, 2019)
A Research Report Submitted to the Faculty of Arts and Social Sciences in Partial Fulfillment of the Requirements for the Award of Diploma in Library and Information Science of Kabale University